PEMBELAJARAN MENULIS CERPEN MENGGUNAKAN SNOWBALL THROWING - Lilis Sumaryanti (MUADDIB Jurnal Kependidikan dan Keislaman, 2014)
Writing can lead students to acquire and develop the power of reason. Therefore, learning to write must be done correctly to students from low-grade. The selection of appropriate learning media and methods as well as the variety of learning models will assist students in improving writing short stories. One way to improve students' skills of writing short stories is the use of models of snowball throwing. In fact there are many obstacles in learning to write short stories and is still oriented toward purely theoretical. Low interest teachers and students to learn to write, especially write short stories as well be one cause. Similarly, in the SDN Janti Slahung Ponorogo especially for students in grade V. Learning to write short stories have not been able to work as expected because 80% of grade V students learn to write student achievement is low, the value of Indonesian KKM 70.00 has not been achieved. To overcome these problems, the authors find a solution to save a way of throwing a snowball models packed in a class action research (PTK) of the cycle phases. Learning model used in this study and the model of snowball throwing fun it brings results. It can be seen from the results of student learning to write short stories I persiklus the cycle reaches the average value of 69.00 at the end of the second cycle, while the average achievement of students increased to 76.75 with 100% completeness. An increase in student achievement and motivation in learning to write short stories using the model of snowball throwing, this is evident from the sight of people exiting and student learning outcomes.